Transformatory learning in nurse education - Freshwater, Dawn (1998)
This study aimed to explore the effects of a transformatory learning programme in a group of Project 2000 nursing students. A secondary focus of the study was to monitor the effectiveness of reflexive action research as a tool for reducing the theory-practice gap that persists between nurse education and nursing practice. The learning programme was developed around the process of reflection and evaluated within a framework of a hierarchical model of nursing research and critical social theory.